Facile Synthesis of CuO/ITO Film Via the Chronoamperometric Electrodeposition for Nonenzymatic Glucose Sensing - Tran, Duong Thi Thuy; Nguyen, Dung Quoc; Pham, Chuyen Hong; Tran, Lam Dai; Nguyen, Dai Tien (Communications in Physics, 2020)
We report on the synthesis of copper (II) oxide (CuO)/indium tin oxide (ITO) electrode via the electrochemical deposition method using a CuSO4 solution and then thermal oxidation in air at temperature of 400 oC for 2 h. The crystalline structure and morphology of CuO were characterized by scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD). The electrochemical properties of the CuO/ITO electrode to glucose in the alkaline medium of 0.1 M NaOH solution were investigated by cyclic voltammetry (CV) and Chronnoamperometry. The CuO-N/ITO electrode showed the best electrochemical properties for glucose detection in comparison to the others. Chronnoamperometry of CuO-N/ITO electrode to the glucose response showed excellent stability, the linear range of 1 mM to 3600 mM with high sensitivity of 283.6 mAcm-2mM-1 and 0.61 mM of the detection limit (S/N=3). A good response of the CuO-N/ITO electrode, which was investigated for different human serum samples, indicates a high potential of its towards a glucose sensor for analysis in real examples.